Analysis of Waterfall and Agile Scrum Approaches in Information Technology Project Management - Sahputra, Eko Siswo Adi; Syibaihi, Ahmad; Alamsyah, Bayu; Azhari, Ahmad Fakhry; Shobiha, Siti (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Project management in the field of information technology (IT) requires an appropriate methodological strategy to ensure successful implementation. Two commonly applied approaches are the Waterfall method and Agile Scrum. This article presents a comprehensive analysis of the fundamental differences, advantages, and limitations of these two methodologies within the context of IT project management. Based on a review of recent literature, this study emphasizes that the choice of methodology should be aligned with the project's characteristics, available resources, and the potential variability of user requirements. Agile Scrum is considered more responsive to changing conditions, while Waterfall is better suited for projects with stable and well-defined requirements. The findings of this study aim to provide strategic insights for project managers in selecting the most appropriate implementation approach.